Peningkatan Kapasitas Aparatur Desa dalam Pengelolaan Dana Desa: Studi di Desa Gampong Baro KB Aceh Barat - Herman Rahayu Meulaboh; Isnan Hari Mardika; Iwan Rianto Setiadi (Universitas Katolik Soegijapranata, Semarang, 2026)
Village development plays a crucial role in achieving the welfare of the Indonesian people, with Village Funds serving as a key instrument to improve public services, empower communities, and support infrastructure development. The effectiveness of Village Fund utilization largely depends on the accountability of its management. In Gampong Baro KB Village, Woyla Timur District, West Aceh Regency, the preparation of annual financial plans (RKPDes and APBDes) often faces delays due to the limited capacity of village apparatus. Village officials have difficulties understanding the financial management system, including planning, administration, bookkeeping, and reporting, which results in delays in monthly administrative procedures.This study aims to enhance the capacity of village apparatus in managing Village Funds transparently and accountably through capacity-building training. The expected outcomes include improved efficiency, better compliance with administrative requirements, and higher quality in Village Fund management. The research uses a qualitative descriptive method with an action-oriented or capacity-building approach, focusing on strengthening the abilities of village officials to manage funds more transparently and accountably. Village Fund planning and budgeting are carried out through Village Meetings and Village Development Planning Meetings (Musrenbang), formalized in the Village Government Work Plan (RKPDes), and allocated in the Village Budget (APBDes). Reporting and accountability are implemented transparently using the Village Financial System, ensuring proper fund management and compliance with regulations.